Peran Pengungkapan Pendapatan Komprehensif Lain Memoderasi Pengaruh Pengungkapan Emisi Karbon dan Keragaman Dewan Direksi Terhadap Manajemen Laba - Muhammad Fayad Zukhruf Umagap; Vinola Herawaty (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study examines the effect of Carbon Emissions Disclosure and Board Diversity on Earnings Management, with Other Comprehensive Income Disclosure as a moderating variable. The sample consists of 51 energy companies listed on the Indonesia Stock Exchange for the 2021–2023 period, selected using purposive sampling. Data were obtained from financial statements, annual reports, and sustainability reports. The results show that Carbon Emissions Disclosure has a negative and significant effect on Earnings Management, Board Gender Diversity does not have a negative effect on Earnings Management, Board Nationality Diversity has a negative but insignificant effect on Earnings Management, and Other Comprehensive Income Disclosure has a positive and significant effect on Earnings Management. Furthermore, Other Comprehensive Income Disclosure strengthens the negative effect of Carbon Emissions Disclosure on Earnings Management and weakens the negative effect of Board Gender Diversity and Board Nationality Diversity on Earnings Management.